2016
DOI: 10.1007/s10792-016-0393-2
|View full text |Cite
|
Sign up to set email alerts
|

Red reflex examination in neonates: evaluation of 3 years of screening

Abstract: Our results are consistent with the previous findings, although reports on red reflex screening are sporadic in the literature. Despite the high number of false positives, the red reflex test has proven to be a useful, easy to perform and low cost test for the early detection of congenital low vision diseases, and our data confirm that it must become part of normal neonatal assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 19 publications
2
20
0
1
Order By: Relevance
“…7 However, our data show that RB is a relatively uncommon diagnosis in patients who present with ARR when compared with other diagnoses. This is consistent with prior studies that cite the incidence of RB to be between 0.005% 8 and 0.06%. 9 Since detecting an ARR in patients with RB can be difficult, with sensitivity estimates ranging from 16% for peripheral lesions viewed directly 10 to 96% for large lesions viewed obliquely, 11 prompt referral to an ophthalmologist remains critical if leukocoria is a concern to exclude RB as well as other vision-threatening pathologies.…”
Section: Discussionsupporting
confidence: 93%
“…7 However, our data show that RB is a relatively uncommon diagnosis in patients who present with ARR when compared with other diagnoses. This is consistent with prior studies that cite the incidence of RB to be between 0.005% 8 and 0.06%. 9 Since detecting an ARR in patients with RB can be difficult, with sensitivity estimates ranging from 16% for peripheral lesions viewed directly 10 to 96% for large lesions viewed obliquely, 11 prompt referral to an ophthalmologist remains critical if leukocoria is a concern to exclude RB as well as other vision-threatening pathologies.…”
Section: Discussionsupporting
confidence: 93%
“…A study done by Romano P E et al [2] found Brückner test (a Red Reflex Test where both eyes are visualized simultaneously using a Direct Ophthalmoscope) to be a effective method in infants to screen for visual acuity, binocular acuity and ocular pathology. The study done by Cagini C et al [3] reported that in Umbria , during the study period, 22,884 live births were reported and of them, 22,272 new born were subjected to RER. In that study, RER Test was done on 22,272 (97.3%) children out 22884 who were born in Umbria, Italy over a span of 3 years of study (2012)(2013)(2014), out of which 461 neonates (4.83%) were found to be having an equivocal or positive test results who were then referred to higher centre where three neonates were found to be affected by an important ocular pathology ( two diagnosed with retinoblastoma and one diagnosed with congenital cataract).…”
Section: Discussionmentioning
confidence: 99%
“…Common causes of preventable blindness among neonates includes Congenital cataract, High refractive error, Strabismus, Congenital glaucoma, retinal abnormalities like retinoblastomas, Retinopathy of prematurity and amblyopia . For all the ocular abnormalities, Red Eye Reflex test plays key screening tool for their early screening with high sensitivity as mentioned in previous studies conducted in developed countries [2][3][4][5]. The Red Reflex is described as the red to orange reflection of light from the fundus of the eye, observed while using a retinoscope or an ophthalmoscope.…”
Section: Introductionmentioning
confidence: 99%
“…За таких умовах пошук простих методів, які б дали змогу групувати пацієнтів та визначити терміновість огляду, набуває особливого значення. Протягом останнього часу багато уваги приділено вивченню можливостей діагностики очної патології за допомогою «рожевого рефлексу» з очного дна [1,7,8].…”
Section: обговоренняunclassified